KONTRIBUSI ISLAM TERHADAP PERADABAN BARAT - asmuni asmuni (IAIN Syekh Nurjati Cirebon, 2017)
Allah Almighty has created man as the most perfect being. Human perfection in the creation of its form, coupled with the giving of reason, then obviously human beings have a high level compared with other creatures. There are many graces of Allah SWT to human being, among them is the gift of reason. By the gift, people are able to think and to create and also to develop civilization. Islamic civilization reached the peak point and able to penetrate the mainland of Europe. The reality in turn has been a testament of how Islamic civilization has influenced Western civilization. The influence of Islamic civilization resulted the growth of new initiatives, creativity and productivity of higher quality that marked the existence of a model of civilization that is vibrant, dynamic, visionary and have a clear future orientation. And this is what in history is considered as an Islamic contribution to Western civilization.Keywords: Islam, Civilization, Islamic Civilization, and Western Civilization